Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5897/ajar2014.8617
|View full text |Cite
|
Sign up to set email alerts
|

Choice of alternative crop enterprises among smallholder tobacco farmers in Teso District, Kenya: A multinomial logit analysis

Abstract: The study analysed the factors affecting the choice of alternative crop enterprises among smallholder tobacco farmers in Teso district, Kenya, using Multinomial logit model. Data used for the study were obtained from primary sources through structured questionnaires using a multistage sampling technique from 150 farmers selected randomly. The results indicate that farmers are indeed reducing the acreage under tobacco and venturing into other alternative crops. This shift and the choice of the alternative gone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Multinomial logit (MNL) is a widely used model in biomedical, econometrics and social science studies to explain the choice of an alternative among a set of exclusive alternatives (Wanyama et al, 2010;El-Habil, 2012;Mbaye et al, 2014;Peng and Nichols, 2003). Generally, the MNL Model defines probabilities as a function of Xi of the unknown parameter, and the model parameters are typically estimated by the maximum likelihood (ML) method (El-Habil, 2012;Peng and Nichols, 2003;Hoffman and Duncan, 1988) For this study, the four sources of postharvest tomato losses indicated by farmers were losses at the farm-gate, transportation of the produce, storage, and marketing.…”
Section: Multinomial Logit Regression Model For Determining Factors I...mentioning
confidence: 99%
“…Multinomial logit (MNL) is a widely used model in biomedical, econometrics and social science studies to explain the choice of an alternative among a set of exclusive alternatives (Wanyama et al, 2010;El-Habil, 2012;Mbaye et al, 2014;Peng and Nichols, 2003). Generally, the MNL Model defines probabilities as a function of Xi of the unknown parameter, and the model parameters are typically estimated by the maximum likelihood (ML) method (El-Habil, 2012;Peng and Nichols, 2003;Hoffman and Duncan, 1988) For this study, the four sources of postharvest tomato losses indicated by farmers were losses at the farm-gate, transportation of the produce, storage, and marketing.…”
Section: Multinomial Logit Regression Model For Determining Factors I...mentioning
confidence: 99%